2021
DOI: 10.1177/02698811211026454
|View full text |Cite
|
Sign up to set email alerts
|

Lasting effects of a single psilocybin dose on resting-state functional connectivity in healthy individuals

Abstract: Background: Psilocybin is a psychedelic drug that has shown lasting positive effects on clinical symptoms and self-reported well-being following a single dose. There has been little research into the long-term effects of psilocybin on brain connectivity in humans. Aim: Evaluate changes in resting-state functional connectivity (RSFC) at 1 week and 3 months after one psilocybin dose in 10 healthy psychedelic-naïve volunteers and explore associations between change in RSFC and related measures. Methods: Participa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 165 publications
(142 reference statements)
0
28
0
1
Order By: Relevance
“…Previous studies in HCs showed that psilocybin (2 mg) IV destabilized a frontoparietal subsystem (293), whereas IV LSD (75 µg) and IV psilocybin increased the fractal dimension of bold blood oxygen level dependent (BOLD) time-series from regions assigned to the dorsal-attention network (294). Furthermore, a recent rsFC fMRI study in 10 healthy volunteers showed that the executive control network was decreased at 1-week, which was associated with increased mindfulness at 3 months, but there were no other significant changes in other networks (295).…”
Section: Neural Circuitrymentioning
confidence: 99%
“…Previous studies in HCs showed that psilocybin (2 mg) IV destabilized a frontoparietal subsystem (293), whereas IV LSD (75 µg) and IV psilocybin increased the fractal dimension of bold blood oxygen level dependent (BOLD) time-series from regions assigned to the dorsal-attention network (294). Furthermore, a recent rsFC fMRI study in 10 healthy volunteers showed that the executive control network was decreased at 1-week, which was associated with increased mindfulness at 3 months, but there were no other significant changes in other networks (295).…”
Section: Neural Circuitrymentioning
confidence: 99%
“…Whereas most of these studies investigated acute effects of psilocybin on functional network connectivity, one study on 10 healthy volunteers evaluated the effects of a single psilocybin administration on functional connectivity of the executive control network (ECN) one week and three months after intake. The significant decrease in ECN functional connectivity after one week of administration of psilocybin was not evident after three months [62].…”
Section: Pharmacological Neurobiological and Neuroimaging Findingsmentioning
confidence: 80%
“…The current study examined only acute psilocybin effects on dynamic functional connectivity, while previous studies indicate that psilocybin induces lasting changes in clinical symptoms, mood, and core personality traits. To date, three studies have examined long-term psilocybin effects on functional brain imaging, both primarily examining static connectivity measures (Barrett et al, 2020;Doss et al, 2021;McCulloch et al, 2021b). Two of these studies analyzed dynamic conditional correlation (Engle, 2002) as a variance measure of edge-specific correlation coefficients (Barrett et al, 2020;Doss et al, 2021).…”
Section: Discussionmentioning
confidence: 99%